The theoretical modelling of a suction caisson foundation using hyperplasticity theory - Lam, N; Houlsby, G (2005)
A theoretical model for the analysis of suction caison foundations, based on a thermodynamic framework (Houlsby and Puzrin 2000) and the macro-element concept is presented. The elastic-plastic response is first described in terms of a single-yield-surface model, using a non-associated flow rule. To capture hysteresis phenomena, this model is then extended to a multiple yield surface model. The installation of the caisson using suction is also analysed as part of the theoretical model. Some preliminary numerical results are given as demonstrations of the capabilities of the model. © 2005 Taylor and Francis Group.